Review on measurement techniques and technologies to propose new rating scale measurement for shariah compliant hotel industry in Malaysia - Hazlin Fardila Abdul Hasim; NorHapiza Mohd Ariffin; Mohd Zaki Zakaria (Institute of Advanced Engineering and Science, 2019)
The tourism industry based on the Islamic approach is increasingly accepted by the tourists. This paper presents a review of measurement techniques and technologies’ scale measurement for Shariah Compliant Hotel Industry in Malaysia. Since the use of the rating system in Syariah Hotel Industry in Malaysia has yet to be implemented, it is difficult for the industry to determine the status level of a hotel. Furthermore, the consumers are unable to make the right choice based on their own needs. This study aims to propose new Rating Assessment for Scale Measurement system focusing on hotel industry based on Shariah Compliant standard known as Shariah Compliant Hotel Rating Measurement Scale System (SCHRMS). Scale measurement will be used to ensure all the Shariah Compliant Certificates are certified with certain level and follow the same standard. Multiple characteristics and categories must be clarified or considered when processing rating assessment for Shariah Compliance (SC) hotel. To solve the multiple characteristics’ issues, Fuzzy Analytic Hierarchy Process will be used. The process is accurate and suitable for selecting various types of information and can be used as a decision-making tool because it controls uncertain and inaccurate data. The raw data obtained from questionnaires as well as structured and unstructured interview will be analyzed using Rasch Analysis Method. Only this method is will be able to comply to the five main principles of analysis for a more meaningful and accurate conclusion of the research data obtained. Through this system that will developed, the problem related to rating measurement for SC hotel will be solved. The SC hotel rating system will be parallel to the conventional based hotel. The system is accepted for the convenience of Muslims as well as non-Muslims globally.